2009
DOI: 10.1007/s11746-009-1495-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saturated/Unsaturated Fatty Acid Ratio on Physicochemical Properties of Palm Olein–Olive Oil Blend

Abstract: Although blending polyunsaturated oil with more saturated or monounsaturated oils has been studied extensively, there is no similar information regarding the partial replacement of palm olein with olive oil (OO). Therefore the main objective of this study was to investigate the effects of OO partial replacement (0, 25, 50, 75, 90 and 100% w/w) on the chemical stability of palm olein oil (POO). The physicochemical properties of oil samples namely iodine value, peroxide value (PV), anisidine value, TOTOX value (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 24 publications
(30 reference statements)
4
22
0
2
Order By: Relevance
“…This is because of its moderately low linoleic acid content is remarkably appropriated for blending with the unsaturated oils. [18,19] POO consists 38.3% of palmitic, 42.1% of oleic, and 10.6% of linoleic acids, and it is also the leading potential source of tocols, representing 70% of tocotrienols and 30% of tocopherols. Previous studies reported that tocols, natural vitamin source, in POO acts as an antioxidant and allow a longer/quality shelf-life for fried foodstuffs.…”
Section: International Journal Of Food Propertiesmentioning
confidence: 99%
“…This is because of its moderately low linoleic acid content is remarkably appropriated for blending with the unsaturated oils. [18,19] POO consists 38.3% of palmitic, 42.1% of oleic, and 10.6% of linoleic acids, and it is also the leading potential source of tocols, representing 70% of tocotrienols and 30% of tocopherols. Previous studies reported that tocols, natural vitamin source, in POO acts as an antioxidant and allow a longer/quality shelf-life for fried foodstuffs.…”
Section: International Journal Of Food Propertiesmentioning
confidence: 99%
“…Abdulkarim SM, Myat MW, Ghazali HM, et al (2010 conjugated oxidative products, owing to its high linoleic acid content.…”
Section: Referencesmentioning
confidence: 99%
“…To overcome the problem of poor oxidative stability (OS) of soybean oil, ways of modifying fatty acid composition and increasing natural antioxidants were sought, such as combining high-oleic sunflower oil with corn oil or hydrogenated soybean oil with soybean oil (Abdulkarim et al, 2010;Naghshineh et al, 2010) or combining palm-olein with soybean oil (Warner and Gupta, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The 70:30 w/w MoO/PO blend was found to contain the highest amount of unsaturated FA 72.76 which may be considered having better oxidative stability and characteristics compared to PO alone and other MoO/PO blending ratio. Naghshineh et al 12 reported that the partial replacements of C16:0 with C18:1 resulted in the least increment in total polar content TPC and viscosity of the oil blend after frying. High oleic acid oils have been proven to be high resistant to thermal oxidative rancidity during frying 5 .…”
Section: Fa Compositionmentioning
confidence: 99%